Nutritional and organoleptic quality of brown rice based nutri-bar during ambient storage: Nutritional evaluation of brown rice based nutr-ibar - Sood, Monika; Nishu; Bandral, Julie D; Gupta, Neeraj; Sheetal (ORYZA-An International Journal of Rice, 2024)
The present investigation was carried out with the objective to assess the nutritional and organoleptic quality of brown rice based nutri-bar during storage period of 90 days. Varied percentages of brown rice, oats and flaxseeds were mixed together to form seven different treatment combinations. For the development of nutri-bar brown rice, oats and flaxseeds were blended in the ratios of 100:00:00, 85:5:10, 80:10:10, 75:15:10, 70:20:10, 65:25:10 and 60:30:10 per cent, respectively. Prepared treatments of nutri-bar were packed in aluminium laminates and stored under ambient storage conditions. The quality of nutri-bar was assessed for its nutritional and organoleptic parameters at 30 days interval until 90 days. The highest mean crude protein (12.11 %), crude fat (8.59 %), crude fibre (6.42 %), ash (2.49 %), iron (6.44 mg/100g), calcium (82.21 mg/100g) and potassium (447.34 mg/100g) were recorded in treatment T7 (60:30:10:: Brown rice: Oats: Flaxseeds), whereas treatment T1 (100:00:00:: Brown rice: Oats: Flaxseeds) recorded highest carbohydrates of 75.69 per cent. On the basis of organoleptic evaluation, the highest mean overall acceptability score of 7.82 was recorded in T5 (70:20:10:: Brown rice: Oats: Flaxseeds) and was adjudged as superior among all the treatments of nutri-bar. Thus, nutritious bar can be developed by incorporating 20% oats and 10% flaxseed with 70 % brown rice.